МІНЛИВІСТЬ РЕПРОДУКТИВНОГО ПОТЕНЦІАЛУ ЧОРНОМОРСЬКОГО ШПРОТУ (SPRATTUS SPRATTUS PHALERICUS) У ЗВ'ЯЗКУ З ТЕМПЕРАТУРНИМИ УМОВАМИ ДОВКІЛЛЯ - Гірагосов, В. Є.; Зуєв, Г. В.; Репетін, Л. Н. (Marine Ecological Journal, 2023)
The results of the study of the inter-annual and intra-annual (seasonal) variability of several individual and population reproductive parameters of the Black Sea sprat Sprattus sprattus phalericus (Risso, 1826) from the water area of the south-western coast of Crimea are presented. Basis of reproductive potential – 80.3 % of the total number of individual simultaneous spawning – takes place within two months – December and January. Overall duration of the spawning season varies from 4.6 to 5.8 months during different years. Optimal spawning temperature limits were specified as 7 – 12°С. The concept of the "most favorable spawning temperature" (8 – 9°С) was suggested, within the limits of which 56.1 % of the total simultaneous spawning were registered. Near positive correlation between the spawning activity (spawning frequency) and average water temperature during winter season was revealed and proposed as a predictor for assessment of the population reproductive potential and commercial stock of the sprat.